The Role of Parents in Instilling Islamic Educational Values in Deaf Children at SLB ABC Melati Aisyiyah Tembung - Rangkuti, Rini Antika Sari; Pulungan, Enny Nazrah (FKIP - Universitas Riau, 2025)
This study aims to examine the role of parents in instilling Islamic values in deaf children and the obstacles encountered in the process of religious education at SLB Melati Aisyiyah Tembung. Employing a qualitative approach with a descriptive research design, data were collected through observation, in-depth interviews, and documentation involving 11 parents (8 males and 3 females) selected using a purposive sampling technique. Observations were conducted to identify parents’ activities in supporting the learning of deaf children, while interviews explored their strategies and roles in instilling Islamic values, complemented by documentation in the form of photographs and activity records. Data were analyzed using thematic analysis through data reduction, data presentation, and conclusion drawing. The findings reveal that parents play a crucial role through visual approaches and direct practice, although challenges such as limited communication skills, insufficient educational resources, and lack of environmental support persist. The study concludes that strong collaboration among families, schools, and communities is essential to create an inclusive educational environment and to foster the development of Islamic values in children with special needs, while also highlighting the need for targeted training programs and accessible learning materials to optimize religious education for deaf children.